2015
DOI: 10.1371/journal.pone.0139575
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Enterobacteriaceae and Calcium Oxalate Deposits

Abstract: BackgroundThe role of calcium oxalate crystals and deposits in UTI pathogenesis has not been established. The objectives of this study were to identify bacteria present in pediatric urolithiasis and, using in vitro and in vivo models, to determine the relevance of calcium oxalate deposits during experimental pyelonephritis.MethodsPediatric kidney stones and urine were collected and both cultured and sequenced for bacteria. Bacterial adhesion to calcium oxalate was compared. Murine kidney calcium oxalate deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 44 publications
7
88
0
4
Order By: Relevance
“…Other work has examined the vaginal microbiome in relation to age, in particular around menarche. Most have found that Lactobacillus species are less common before menarche, but there is a rapid transition to the “adult-type” microbiome dominated by Lactobacillus [16••, 17, 18]. However, Hickey et al recently found that the majority of vaginal microbiome samples showed a predominance of Lactobacilli in all ages, including premenarcheal girls, which is similar to previously reported microbiome makeup of both postmenarcheal girls and adult women.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other work has examined the vaginal microbiome in relation to age, in particular around menarche. Most have found that Lactobacillus species are less common before menarche, but there is a rapid transition to the “adult-type” microbiome dominated by Lactobacillus [16••, 17, 18]. However, Hickey et al recently found that the majority of vaginal microbiome samples showed a predominance of Lactobacilli in all ages, including premenarcheal girls, which is similar to previously reported microbiome makeup of both postmenarcheal girls and adult women.…”
Section: Introductionsupporting
confidence: 62%
“…While authors note that this discrepancy could be partially explained by the ability of the antibiotics to more effectively target bacteria in urine than those within the biofilm of the stones, authors postulate that calcium oxalate stones harbor a microbiome that is independent from that of the surrounding urine. Further, they postulate that the bacteria within the stone’s microbiome contribute to stone formation by altering urine supersaturation [16••]. Taken together, these data suggest that it may be possible that the stone microbiome could be predictive of stone recurrence; however, this possibility has yet to be studied.…”
Section: Urolithiasismentioning
confidence: 99%
“…urinary stones. Investigators are beginning promising research to evaluate the FUM of these and other populations [1,4,3741]. …”
Section: Introductionmentioning
confidence: 99%
“…
№2 (54) 2017Український журнал нефрології та діалізу Оригінальні наукові роботи ВСТУП. Як відомо, основою лікування інфекції сечової системи (ІСС) загалом та пієлонефриту, зокрема, є антибактеріальна терапія [1,4]. Проте, на сьогодні є доведеним, що застосування антибіотиків призводить до виражених короткострокових та довгострокових порушень біоценозу кишківника з неповним відновленням мікробіоти до вихідного складу на протязі декількох років [2,10].
…”
unclassified
“…У попередніх дослідженнях нами було продемонстровано, що постійне застосування антибактеріальних лікарських засобів, у тому числі й довготривала антибіотикопрофілактика у хворих на рецидивуючий пієлонефрит, порушує видовий та кількісний склад мікробіоти кишківника з істотним знищенням Lactobacillus spp. та формуванням гіпероксалурії [1,78]. Разом з тим, вплив застосування антибіотиків, які найчастіше використовуються для лікування пацієнтів з ІСС, на кількісний склад Lactobacillus spp.…”
unclassified